Understanding Teachers’ Perceptions and Experiences of Organizational Culture and Its Influence on Job Satisfaction: A Qualitative Study in Penang National School - Xu Jia; Muhammad Aufa Ihsan; Abdurrahman Thalib (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study explores teachers’ perceptions and experiences of organizational culture and its influence on job satisfaction in a national primary school in Penang, Malaysia. Using an interpretive qualitative case study design, data were collected through semi-structured interviews, focus group discussions, and document analysis involving 18 participants. The findings reveal four main dimensions of organizational culture that shape teacher job satisfaction: leadership and participation, collegial relationships, recognition and professional growth, and work environment and conditions. Although teachers generally perceived the school culture as supportive and collaborative, the study identified several tensions, including limited participation in school-level decision-making, unequal access to professional opportunities, and psychological pressure caused by workload and administrative demands. A key contribution of this study is the identification of a participation gap, referring to the contrast between teachers’ autonomy in classroom instruction and their limited influence on broader organizational decisions. The study also shows that seniority and hierarchical position shape how teachers experience organizational culture. These findings suggest that teacher job satisfaction is influenced not only by physical resources and collegial support but also by meaningful participation, psychological well-being, and equitable professional development. The study offers practical implications for school leaders in developing a more inclusive, transparent, and supportive organizational culture.